The Steady-State and Dynamic Characteristics of a Humidity-Sensitive Air Inlet: Modeling Based on Measurements - Maciej Mijakowski; Piotr Narowski (Energies, 2025)
This paper presents the airflow characteristics of humidity-sensitive air inlet. This type of air inlets and exhausts are often part of demand control ventilation, especially in dwellings where humidity is an important indicator of ventilation needs. Humidity-controlled ventilation is one of the simplest implementations of smart ventilation, even in the case of a natural ventilation system. This type of solution leads to decreased energy consumption and increases the indoor air quality. A description of airflow characteristics is crucial for resolving these issues. The presented characteristics are based on the measurements of the indoor/outdoor relative humidity, airflow, and pressure drop across the air inlet. The characteristics are described based on a general power law flow model (V = C·∆pn), which is the most suitable, for example, for the CONTAM multizone indoor air quality and ventilation analysis computer program. The characteristics include relationships between the indoor and outdoor relative humidity, hysteresis, and dynamic changes in indoor relative humidity. The simplified and complex formulas are presented. The accuracy of the airflow calculation based on these formulas is discussed.